A CGE Analysis of the Economic Impact of Trade Liberalisation on the Algerian Economy - Touitou, Mohammed (European Journal of Sustainable Development, 2016)
The principal focus of the study is to show the nature and extent of the incentives trade policy liberalisation could provide on the way to further boost the economy of Algeria. It also tries to find out what the economic position would be, should the trade regime be more or fully liberalisation by reducing or elimination the existing tariff. In this study, different types of external price shocks are also considered in order to test the response of the economy. Model results indicate that by reducing tariffs, domestic output increase in almost all the sectors but government revenue and saving decline significantly. Government revenue fall due to the reduction/elimination of tariff could be compensated by reducing net subsides to the corporate sector and also by increasing income tax in a progressive way. Exports also increase showing the justification of the liberalisation and also supporting the argument that tariffs bias exports. But the increase in total import is bigger than the increase in exports which causes a deterioration of the real balance of trade, but the elimination of tariff increase private consumption and total absorption. Export price shocks in petroleum sectors chow a fall in domestic output and consequently a fall in value added and total employment. Domestic terms of trade of exports deteriorate and exports fall. This also causes a fall in GDP, private consumption and total absorption. The government revenue declines and budget deficits worsen. A 10 percent devaluation in the real exchange rate shows a fall in domestic output in aggregate agriculture and service whereas an increase in output in industry. GDP at factor cost also falls simultaneously with a fall in total absorption and private consumption. Devaluation pushes up exports in the majority of the sectors and brings down import in some sectors only. Keywords: External Shocks, trade policies, Algerian Economy, Computable General Equilibrium Model.